The Role Of Negotiation Strategies In The Success Of AHP (Hierarchical Analysis Processes) To Decision-Making - قاسم سامر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
the study aimed to determine the impact of negotiation strategies represented by (cooperative strategy, competitive strategy, combat strategy, dependency strategy) on the success of AHP processes, hierarchical analysis method) for decision-making in the Syrian Oil Transport Company. The researcher followed the descriptive and analytical approach in his study, and a set of methods, including relying on secondary and primary data through a questionnaire designed, and he reviewed a set of hierarchical decision-making (AHP) applications in a group of international companies The study found a set of results, including: An acceptable significant effect of negotiation strategies was found on the success of the hierarchical analysis method (AHP) for decision-making, as the value of the correlation coefficient was 0.752, and Sig = 0.000, and this is confirmed by the four sub-hypotheses, and that negotiation strategies are very important for the company; Where negotiation strategies, if they are followed by the company, play a major role in the success of the AHP decision-making method.